Tingkat Keterjadian Penyakit Layu Stewart pada Benih dan Respon beberapa Varietas Jagung terhadap Infeksi Pantoea stewartii subsp. stewartii - Haliatur Rahma; Meity S Sinaga; Memen Surahman; Giyanto . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Disease incidence of Stewart’s wilt on the seed and response of several maize varieties to Pantoea stewartii subp. stewartii. Stewart’s wilt disease of maize is caused by Pantoea stewartii subsp. stewartii. This bacterium is seed-borne pathogens, when attacked maize caused yield lost 40-100%. The objective of this research was to detemine the incidence level of stewart’s wilt disease, growth of some varieties of maize and their response to stewart’s wilt pathogens Pantoea stewartii subsp. stewartii. The research was conducted in the Laboratory of Bacteriology and Greenhouse Cikabayan IPB from November 2011 to March 2012. In experiment I, nineteen samples of maize were used for symptom test in the maize seedling stage, using Randomized Block Design with three replications. Experiment II used a Randomized Block Design with 2 factors: maize varieties (8 hybrids varieties, 3 open pollinated varieties, and 7 sweet corn varieties) and bacteria isolates (BGR 2, BGR 4, BGR 28, BGR7 and PSM 27), with three replications. The results showed in experiment I, the incidence of stewart’s wilt disease ranged 2.00 – 15.33%, germination and vigor index of maize seed were 68.00 – 95.33% and 55.33 – 90.67% respectively. While in experiment II, hybrid and open pollinated of maize varieties were resistant to moderately susceptible while all sweet corn varieties were susceptible to infection of Pantoea stewartii subsp. stewartii.